Talaromyces spp. are tunable producers of light-activated secondary metabolites with anticancer potential - Angelika Seeber; Vanessa Kern; Carmen Bendetta; Stefanie Merkel; Markus Meitinger; Simone Moser; Pamela Vrabl; Bianka Siewert (Journal of Photochemistry and Photobiology B: Biology, 2026)

Perspective on yeast-3-hybrid assays for target identification of bioactive natural products - Jonas A. Stehlin; Claudia Ascher; Simone Moser (Phytochemistry Reviews, 2026)
While an immense number of natural products have been screened for bioactivity using a variety of phenotypic assays, elucidation of their protein targets remains a significant bottleneck limiting further clinical research. Next to conventional pulldown assays and modern developments, such as cellular thermal shift assays (CETSA), yeast three-hybrid (Y3H) has emerged as a powerful yet underutilized tool that provides a low-barrier avenue for target identification of the challenging natural products space. Still, adoption of Y3H in natural products research has been slow in spite of successful target identification of a diverse range of small molecules reported in literature. In this perspective, we present the underlying methodology and its limitations as well as possible future developments and how it may accelerate and complement the target ID of natural compounds. We encourage natural product researchers to increase efforts on target elucidation of their lead compounds and propose Y3H as an approach, which could be integrated into existing workflows. Graphical abstract

Phyllobilins derived from chlorophyll degradation are overlooked, bioactive phytochemicals in plant-based food - Christian Elvert; Fabian Hammerle; Christian Doppler; David Bernhard; Simone Moser; Cornelia A. Karg (Phytochemistry Letters, 2025)

A bioactive chlorophyll-derived yellow phyllobilin from senescent leaves of Carica papaya (Caricaceae) and its potential role in the ethnopharmacological use of withered leaf extracts - Christian Elvert; Rao Zhigang; Oriol Ruiz-Catalan; Johanna M. Gostner; Andreas Koeberle; Cornelia Karg; Awodayo O. Adepiti; Simone Moser (Phytochemistry Letters, 2025)

Addressing the challenge of protein target identification of bioactive phytochemicals with a yeast-3-hybrid screening - Simone Moser (Phytochemistry Letters, 2025)

Cryptic chlorophyll breakdown in non-senescent green Arabidopsis thaliana leaves - Iris Süssenbacher; Damian Menghini; Gerhard Scherzer; Kathrin Salinger; Theresia Erhart; Simone Moser; Clemens Vergeiner; Stefan Hörtensteiner; Bernhard Kräutler (Photosynthesis Research, 2019)

Reconstructing geographical parthenogenesis: effects of niche differentiation and reproductive mode on Holocene range expansion of an alpine plant - Bernhard Kirchheimer; Johannes Wessely; Andreas Gattringer; Karl Hülber; Dietmar Moser; Christoph C. F. Schinkel; Marc Appelhans; Simone Klatt; Marco Caccianiga; Agnes Dellinger; Antoine Guisan; Michael Kuttner; et al. (Ecology Letters, 2018)
Asexual taxa often have larger ranges than their sexual progenitors, particularly in areas affected by Pleistocene glaciations. The reasons given for this ‘geographical parthenogenesis’ are contentious, with expansion of the ecological niche or colonisation advantages of uniparental reproduction assumed most important in case of plants. Here, we parameterized a spread model for the alpine buttercup Ranunculus kuepferi and reconstructed the joint Holocene range expansion of its sexual and apomictic cytotype across the European Alps under different simulation settings. We found that, rather than niche broadening or a higher migration rate, a shift of the apomict's niche towards colder conditions per se was crucial as it facilitated overcoming of topographical barriers, a factor likely relevant for many alpine apomicts. More generally, our simulations suggest potentially strong interacting effects of niche differentiation and reproductive modes on range formation of related sexual and asexual taxa arising from their differential sensitivity to minority cytotype disadvantage.

A matter of scale: apparent niche differentiation of diploid and tetraploid plants may depend on extent and grain of analysis - Bernhard Kirchheimer; Christoph C. F. Schinkel; Agnes S. Dellinger; Simone Klatt; Dietmar Moser; Manuela Winkler; Jonathan Lenoir; Marco Caccianiga; Antoine Guisan; Diego Nieto‐Lugilde; Jens‐Christian Svenning; Wilfried Thuiller; et al. (Journal of Biogeography, 2016)
Aim Emerging polyploids may depend on environmental niche shifts for successful establishment. Using the alpine plant Ranunculus kuepferi as a model system, we explore the niche shift hypothesis at different spatial resolutions and in contrasting parts of the species range. Location European Alps. Methods We sampled 12 individuals from each of 102 populations of R. kuepferi across the Alps, determined their ploidy levels, derived coarse‐grain (100 × 100 m) environmental descriptors for all sampling sites by downscaling WorldClim maps, and calculated fine‐scale environmental descriptors (2 × 2 m) from indicator values of the vegetation accompanying the sampled individuals. Both coarse and fine‐scale variables were further computed for 8239 vegetation plots from across the Alps. Subsequently, we compared niche optima and breadths of diploid and tetraploid cytotypes by combining principal components analysis and kernel smoothing procedures. Comparisons were done separately for coarse and fine‐grain data sets and for sympatric, allopatric and the total set of populations. Results All comparisons indicate that the niches of the two cytotypes differ in optima and/or breadths, but results vary in important details. The whole‐range analysis suggests differentiation along the temperature gradient to be most important. However, sympatric comparisons indicate that this climatic shift was not a direct response to competition with diploid ancestors. Moreover, fine‐grained analyses demonstrate niche contraction of tetraploids, especially in the sympatric range, that goes undetected with coarse‐grained data. Main conclusions Although the niche optima of the two cytotypes differ, separation along ecological gradients was probably less decisive for polyploid establishment than a shift towards facultative apomixis, a particularly effective strategy to avoid minority cytotype exclusion. In addition, our results suggest that coarse‐grained analyses overestimate niche breadths of widely distributed taxa. Niche comparison analyses should hence be conducted at environmental data resolutions appropriate for the organism and question under study.